2011
DOI: 10.1108/09600031111166438
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the bullwhip effect with order batching in multi‐echelon supply chains

Abstract: Purpose -The purpose of this paper is to analyze the effect of batching on bullwhip effect in a model of multi-echelon supply chain with information sharing. Design/methodology/approach -The model uses the system dynamics and control theoretic concepts of variables, flows, and feedback processes and is implemented using iThink w software. Findings -It has been seen that the relationship between batch size and demand amplification is non-monotonic. Large batch sizes, when combined in integer multiples, can prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 40 publications
1
36
0
Order By: Relevance
“…This research supports the research conducted by Hussain and Drake (2011) in a way that the smallest batch size does not lead to lower amplification. It is also conformity with the findings of (Riddalls and Bennett 2001;Potter and Disney 2006).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…This research supports the research conducted by Hussain and Drake (2011) in a way that the smallest batch size does not lead to lower amplification. It is also conformity with the findings of (Riddalls and Bennett 2001;Potter and Disney 2006).…”
Section: Resultssupporting
confidence: 87%
“…Firstly, it provides an empirical testing of a conceptual study by Hussain and Drake (2011), which analysed the relationship between batch size and the bullwhip effect as non-monotonic and that the size of remainder of quotient determines the value of bullwhip effect. Thus far, there has been no empirical evidence available related to the impact of batch sizing on the bullwhip effect in the existing literature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A notorious family of smoothing replenishment policies is the inventory and order-based production control system (Towill 1982;John et al 1994). Recently, the benefit of this policy has been shown through theoretical studies (Boute et al 2007;Wright and Yuan 2008;Papanagnou and Halikias 2008;Chen and Lee 2009;Zhou et al 2010;Hussain and Drake 2011;Adenso-Diaz et al 2012), as well as empirical researches (Dooley et al 2010;Potter and Disney 2010). However, as we mentioned in Section 1, most of this studies do not consider the impact of this order policy on the customer service level of the supply chain partners.…”
Section: Backgroundsmentioning
confidence: 99%
“…It has been indicated that the bullwhip effect [17] (the magnification of demand variability as orders move up the supply chain) is the culprit behind chaos in inventory levels and production strategies [18]. The negative impacts of the bullwhip effect can be summed up as surplus or short capacities, inadequate customer service, excess inventories, and high inventory costs [18,19]. Therefore, controlling chaos in the SCN is crucial and requires extensive research.…”
Section: Introductionmentioning
confidence: 99%